2005
DOI: 10.1038/sj.bjc.6602393
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of 1- and 2-year screening intervals for women undergoing screening mammography

Abstract: We compared the long-term impact of 1-and 2-year screening mammography intervals using prognostic, screening, and outcome information for women aged 50 -74 years obtained from the Screening Mammography Program of British Columbia in two time periods, prior to 1997 (policy of annual mammography) and after 1997 (biennial mammography). Survival was estimated for both periods using a prognostic model and the expected rate of interval and screen-detected cancers. The likelihood of a screen-detected cancer with annu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
26
0
2

Year Published

2006
2006
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 37 publications
4
26
0
2
Order By: Relevance
“…However, comparing the results of annual and biannual screening over ten years, it was observed that there was an decrease of 1.2% in the specific survival of the women screened biannually. 23 It is noteworthy that this integrative review investigated five-year survival, during which there is a higher tendency for survival. The investigation of survival at ten years or more would probably demonstrate lower rates.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, comparing the results of annual and biannual screening over ten years, it was observed that there was an decrease of 1.2% in the specific survival of the women screened biannually. 23 It is noteworthy that this integrative review investigated five-year survival, during which there is a higher tendency for survival. The investigation of survival at ten years or more would probably demonstrate lower rates.…”
Section: Resultsmentioning
confidence: 99%
“…The publications originated from 20 countries: Korea (six studies), [8][9][10][11][12][13] Japan (five studies), [14][15][16][17][18] Brazil (four studies), 3,[19][20][21] Canada (three studies), [22][23][24] United States (three studies), [25][26][27] Italy (three studies), [28][29][30] Switzerland (three studies), [31][32][33] France (two studies), 34,35 China (one study), 36 Singapore and Sweden (one study, study performed in both countries), 37 Scotland (one study), 38 Spain (one study), 39 Finland (one study), 40 India (one study), 41 England (two studies), 42,45 Mexico (one study), 43 Poland (one study), 44 and the Netherlands (one study). 46 From the aim established for this study, the variables to be investigated were defined: the study design, study site/country, number of subjects, age of the subjects, five year survival rate, disease-free five year survival rate, factors that contribute to the increase in survival rates.…”
Section: Methodsmentioning
confidence: 99%
“…22 The predictive model used was similar to one used previously 31 and was calibrated to the observed impact of prognostic factors on survival in BC. The predicted reduction in breast cancer death in that analysis resulted primarily from the difference in outcomes between screen-detected and interval cancers and the reduction in the proportion of interval cancers in women screened annually.…”
Section: Discussionmentioning
confidence: 99%
“…9,10 However, these studies are small, and turned down by recent studies showing almost similar prognostic characteristics in tumours diagnosed in annual and biennial screening. 11,12 Furthermore, the effect of the screening interval on the mortality from the disease is somewhat unclear. 11,[13][14][15] No randomized trials have compared the effect of annual versus biennial screening intervals, and observational studies on the topic have been limited by small sample sizes and varying definitions of interval cancer.…”
mentioning
confidence: 99%
“…11,12 Furthermore, the effect of the screening interval on the mortality from the disease is somewhat unclear. 11,[13][14][15] No randomized trials have compared the effect of annual versus biennial screening intervals, and observational studies on the topic have been limited by small sample sizes and varying definitions of interval cancer. 9,10,16,17 The costs of annual versus biennial screening will be higher, due to twice as many examinations during the same time period, additional biopsies and a higher number of women probably undergoing emotional distress as a result of false-positive recalls.…”
mentioning
confidence: 99%